The Sayings Gospel Q and the Quest of the Historical Jesus: A Response to John S. Kloppenborg - Cameron, Ron (Harvard theological review, 1996)
John Kloppenborg's article is a superb example of why studies of the gospel tradition, including the Sayings Gospel Q, should be important to students of religion as well as of early Christianity. Beginning with the work of Hermann Samuel Reimarus, whose last anonymous and posthumously published essay on “The Intention of Jesus and His Disciples” inaugurated both the modern quest of the historical Jesus and the origins of the synoptic problem, Kloppenborg traces in an exemplary way the twists and turns of a restless biblical scholarship that continues to struggle with the interpretative challenge laid down by Reimarus. From the pioneering studies of David Friedrich Strauss, Ferdinand Christian Baur, and the Tubingen school, through the detailed analyses of Heinrich Julius Holtzmann, Bernhard and Johannes Weiss, and Adolf von Harnack, to the modern research initiated by Heinz Eduard Tödt, James M. Robinson, Helmut Koester, and Dieter Lührmann, Kloppenborg presents an archaeology of the discipline. His mastery of both primary texts and secondary scholarship demonstrates what is required of anyone who wishes to earn the right to have an opinion.